Pengembangan Pesantren Berbasis Tradisi dan Inovasi: Analisis Emergent Strategy dan Blue Ocean Strategy di Pondok Pesantren Sidogiri Banat 1 - Khoiriyah Khoiriyah; Parmujianto Parmujianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the development strategy of Sidogiri Banat 1 Islamic Boarding School through the perspectives of Emergent Strategy and Blue Ocean Strategy. The research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the development of the pesantren has been carried out gradually, adaptively, and based on community needs without relying on a formal written strategic plan. The strategy emerged as a response to the decline in student enrollment and changing public preferences toward educational institutions that integrate religious and general education. The implementation of the strategy was manifested through the diversification of educational units, including the strengthening of Madrasah Diniyah to Tsanawiyah level, the Islamic Boarding School Equivalency Education Program (PKPPS), and the establishment of the School of Islamic Economics and Business (STEBI). From the perspective of Emergent Strategy, the strategy developed through organizational learning processes, internal deliberation, and values-based leadership. Meanwhile, from the perspective of Blue Ocean Strategy, the pesantren successfully created value innovation through the combination of a salafiyah-based system, formal education, affordable tuition fees, a religious environment, and student security, thereby creating a competitive position distinct from both traditional salaf pesantren and modern Islamic boarding schools. This study concludes that the success of Sidogiri Banat 1 Islamic Boarding School lies in its ability to balance tradition and innovation. This model demonstrates that pesantren possess the capacity to grow as adaptive, competitive, and value-based educational institutions rooted in Islamic traditions.